Bioprospecting of Plant-Beneficial Bacillus Species for Growth Promotion and Disease Suppression - Ruth Meike Jayanti,; Ike Marisna,; jilan Tsani Abdullah,; Suryanti,; Tri Joko, (Tropical Life Sciences Research, 2025)
Plant growth-promoting bacteria (PGPB) have been reported to promote plant growth and protect against plant diseases effectively. PGPB can control plant diseases through direct and indirect mechanisms. The direct mechanism involves the ability to provide nutrients and phytohormones. In contrast, the indirect mechanism refers to the ability to suppress the activity of pathogens through the production of various compounds and metabolites. The purpose of this study is to evaluate the plant health-promoting potential of Bacillus species. Several genetic determinants in 18 isolates of PGPB were investigated via polymerase chain reaction based on the genes fenD, sfp, bamC, ituA, aiiA, ipdC, and nifH. Plant-beneficial traits were confirmed through seedling growth tests and in vitro antagonistic assays in the laboratory, followed by a field experiment that used selected Bacillus isolates to improve plant growth and control twisted disease in shallot. Results revealed that two Bacillus isolates, B-27 and RC76, have potential as PGPB. Isolates B-27 and RC76 were identified as Bacillus velezensis and Bacillus tropicus, respectively, on the basis of gyrB sequence analysis. The application of B. velezensis B-27 by spraying resulted in the lowest intensity of twisted disease in shallot. In addition, combined treatment with B. velezensis B-27 and B. tropicus RC76 increased plant height and leaf number.